BREAKING BOUNDARIES: EXAMINING THE INTERSECTION OF GENDER DISCORDANT NAMES AND SOCIOECONOMIC ATTAINMENT - Roberts, A.L; Rosario, M (Journal of Current Research and Review (JCRR), 2022)
This paper explores the effects of gender discordant names, which are names that are given to individuals of a different gender, on educational attainment and labor market earnings. Using a large administrative dataset from Brazil, a country known for prevalent discrimination against women in employment and prejudice against gender nonconforming individuals, we investigate the consequences of having a name that sends an ambiguous or conflicting signal about a person's gender. Our measure of discordance is based on the percentage of men and women with each first name, ranging from names that send consistent gender signals to names that send ambiguous signals. The results show that both men and women with gender discordant names tend to have lower levels of educational attainment. Additionally, having a gender discordant name is negatively associated with earnings, although the effect diminishes when controlling for education. Specifically, only individuals with the most discordant names continue to experience significantly lower earnings. We further examine a secondary measure of discordance based on the perceived femininity/masculinity of names, obtained from a survey of Brazilians. The analysis reveals that men with less masculine names and women with less feminine names also tend to have lower education and earnings. These findings highlight the disadvantages faced by individuals with gender discordant names, which persist in the long term. The research contributes to the literature on names, signaling, gender stereotypes, and gender measurement. It is particularly relevant in the context of increasing interest in the consequences of gender nonconformity and the recognition of nonbinary genders. By identifying a connection between economic outcomes and subtle variations in perceived gender within a general population sample of adults, our analysis offers a unique perspective in this emerging field of study.